2007
DOI: 10.1074/jbc.m703617200
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization and Actin-bundling Properties of Villin and Its Role in the Assembly of Epithelial Cell Brush Borders

Abstract: Villin is a major actin-bundling protein in the brush border of epithelial cells. In this study we demonstrate for the first time that villin can bundle actin filaments using a single F-actin binding site, because it has the ability to self-associate. Using fluorescence resonance energy transfer, we demonstrate villin self-association in living cells in microvilli and in growth factorstimulated cells in membrane ruffles and lamellipodia. Using sucrose density gradient, size-exclusion chromatography, and matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 55 publications
4
77
0
Order By: Relevance
“…Cerulean-tagged villin was cloned as described previously (34). HeLa GFP-cytochrome c cells were transiently transfected with cerulean-tagged villin, treated with 1 M staurosporine for 0 -5 h, and live cell images captured at different time points (0 -5 h) using confocal laser scanning microscope and a 63ϫ oil objective (LSM 5 PASCAL; Carl Zeiss, Thornwood, NY).…”
Section: Methodsmentioning
confidence: 99%
“…Cerulean-tagged villin was cloned as described previously (34). HeLa GFP-cytochrome c cells were transiently transfected with cerulean-tagged villin, treated with 1 M staurosporine for 0 -5 h, and live cell images captured at different time points (0 -5 h) using confocal laser scanning microscope and a 63ϫ oil objective (LSM 5 PASCAL; Carl Zeiss, Thornwood, NY).…”
Section: Methodsmentioning
confidence: 99%
“…1B, model b). In contradiction with these data George et al [2007] demonstrated that villin can form dimers both in vitro and in vivo [George et al, 2007]. In their model, bundling activity implicates the parallel arrangement of villin dimers mediated by an N-terminal domain, and involves exclusively one ABD in the HP (Fig.…”
Section: Villinsmentioning
confidence: 92%
“…Lily ABP-135 contains six gelsolin-like domains (G1-G6) and a C-terminal headpiece (HP). The asterisk indicates the position of a potential dimerization site [George et al, 2007]. An alternative to a single ABD located between G1 and G2 (ABD1a), is two ABDs located in G1 (ABD1b) and G2 (ABD1c), respectively [Hampton et al, 2008].…”
Section: Villinsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the plant actin-binding proteins such as villin and formin require dimerization for their actin bundling activity (George et al, 2007;Xue et al, 2011). Concerning LIM proteins, one assumption is that LIM domains could dimerize to fulfill their actin-bundling function (Thomas et al, 2007).…”
Section: Lim-domain Proteins Have Been Identified In Several Plantsmentioning
confidence: 99%